Impact of Leadership Culture on Running an Educational Institution - dawoud, Tamara nije (International Journal of Membrane Science and Technology, 2023)
Purpose: The main purpose of the current research paper is based on (a) the identification of the leadership culture in educational institutes and, (b) the investigation of the impact of such leadership culture on successfully running educational institutes. According to the developed research aim, the identified research question was based on making the searches regarding the factors that can leadership culture in the performing educational institute practices. Methods: For developing the answers to the established research topic, the current research uses the primary quantitative survey-based research design with the use of the questionnaire surveys that were distributed among the 100 higher management members in the educational institutes. These educational institutes were identified in the southwest of England, UK. Findings: The findings of the current research mainly indicate the fact that data-driven facts about leadership practices can have a positive impact on running educational institutions. It was further analysed from the developed research results that the culture shifts in the leadership practices of the educational institutions can be brought in when the stakeholders of the educational institutions mainly decided to support the leadership practices. Conclusion: In the end, the paper concludes that the leadership culture in educational institutes must be established in a manner that supports organisational growth in the long run. There are very limited studies which are been conducted on the established topic. Therefore, the current research also recommends that future research be conducted on the mentioned topic.